Sonographic evaluation of plantar fasciitis and relation to body mass index - Ozdemir, H; Yilmaz, E; Murat, A; Karakurt, L; Poyraz, AK; Ogur, E (Elsevier Ireland Ltd, 2005)
Purpose: We have investigated the role of sonography in the diagnosis of plantar fasciitis. Materials and methods: This study evaluates 39 patients with plantar fasciitis and control group of 22 healthy volunteers. The plantar fascia thickness was measured 5 mm distal to the insertion of the calcaneus of plantar aponeurosis. Qualitative parameters such as decreased echogenity, biconvexity, perifascial fluid and calcification of plantar fascia were also noted. Results: Mean plantar fascia thickness was measured 2.9 mm in patients with unilateral heel pain, 2.2 mm for contralateral normal heel and 2.5 mm for control group. There was a statistically significant difference between heel with plantar fasciitis, contralateral normal heel and control groups (p = 0.009 and 0.0001, respectively). Mean body mass index was 28 kg/m(2) in patients with heel pain and 25 kg/m(2) in Control group. Body mass index measurements were significantly different between plantar fasciitis and control groups. We found reduced plantar fascia echogenity in 16 cases (41%), calcaneal spur in 20 cases (51%), biconvex appearance in two cases (5.1%) and perifascial fluid in one case (2.5%). Conclusion: We conclude that in patients with plantar fasciitis, ultrasound may detect relatively small differences in plantar fascia thickness even in clinically unequivocal plantar fasciitis. (c) 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: plantar fasciitis; ultrasound; body mass index